First-in-Human Evaluation of Positron Emission Tomography/Computed Tomography With [18F]FB(ePEG12)12-Exendin-4: A Phase 1 Clinical Study Targeting GLP-1 Receptor Expression Cells in Pancreas - Fujimoto, Hiroyuki; Fujita, Naotaka; Hamamatsu, Keita; Murakami, Takaaki; Nakamoto, Yuji; Saga, Tsuneo; Ishimori, Takayoshi; Shimizu, Yoichi; Watanabe, Hiroyuki; Sano, Kohei; Harada, Norio; Nakamura, Hiroshi; et al. (Frontiers in Endocrinology, 2021)
Pancreatic β-cell mass (BCM) has a central importance in the pathophysiology of diabetes mellitus. Recently, pancreatic β-cell-specific imaging, especially positron emission tomography (PET) with exendin-based probes, has emerged for non-invasive evaluation of BCM. We developed a novel exendin-based probe labeled with fluorine-18, [18F]FB(ePEG12)12-exendin-4 (18F-Ex4) for PET imaging. We subsequently conducted a first-in-human phase 1 study of 18F-Ex4 PET/computed tomography (CT) and investigated the safety and utility for visualizing the pancreas. Six healthy male subjects were enrolled in this study. A low dose (37.0 MBq) of 18F-Ex4 PET/CT was administered (first cohort: n = 2), and subsequently a higher dose (74.0 MBq) was administered (second cohort: n = 4). In the first and second cohorts, 38.6 ± 4.8 and 71.1 ± 4.8 MBq of 18F-Ex4 were administered, respectively. No serious adverse events were observed in both groups. Only one participant in the first cohort showed transient hypoglycemia during the PET scans. 18F-Ex4 PET/CT successfully visualized the pancreas in all participants. The mean standardized uptake value of the pancreas was found to be higher than that in the surrounding organs, except for the bladder and kidney, during the observation. Dosimetry analyses revealed the effective systemic doses of 18F-Ex4 as 0.0164 ± 0.0019 mSv/MBq (first cohort) and 0.0173 ± 0.0020 mSv/MBq (second cohort). 18F-Ex4 PET/CT demonstrated the safety and utility for non-invasive visualization of the pancreas in healthy male subjects. 18F-Ex4 is promising for clinical PET imaging targeting pancreatic β cells.